(untitled) (Al-NASR, 2025)
This study presents a research-based and comparative examination of the doctrine of naskh (abrogation) as discussed in major classical works of ʿUlūm al-Qurʾān. The concept of naskh occupies a central position in Qurʾānic interpretation, as it is directly linked to the understanding of the gradual legislation and evolution of Islamic rulings. Focusing on four seminal works—al-Nāsikh wa al-Mansūkh by Abū ʿUbayd al-Qāsim b. Sallām, al-Burhān fī ʿUlūm al-Qurʾān by Imām al-Zarkashī, al-Itqān fī ʿUlūm al-Qurʾān by Jalāl al-Dīn al-Suyūṭī, and al-Fawz al-Kabīr fī Uṣūl al-Tafsīr by Shāh Walī Allāh al-Dihlawī—this research analyzes how the understanding of naskh developed across different scholarly periods. The study critically compares definitions, classifications, sources of evidence, and the determination of abrogated verses, highlighting the shift from a broad early conception of naskh to a more restricted and methodologically cautious approach in later scholarship. The findings demonstrate an intellectual evolution in Qurʾānic studies, marked by increasing precision, critical scrutiny, and emphasis on the wisdom and objectives underlying legislative change. This comparative analysis contributes to a clearer and more nuanced understanding of naskh as a disciplined and carefully regulated principle within Qurʾānic interpretation.